Nepal : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This Selected Issues paper on Nepal measures the extent to which Nepal's households change their expenditure patterns and labor supply in response to remittances, using the Nepal Household Risk and Vulnerability Survey-2016 and employing a propensity score matching method. This study provides stylized facts on migrant workers and remittance-recipient households (HH), and then analyzes the effect of remittances on HHs' expenditure patterns and labor supply. Reliance on remittances, both at the macro and household levels, makes Nepal highly vulnerable to shifts that could diminish remittance inflows. The slowdown in growth of remittances has been significant since 2016, owing to weak economic performance in major remittance-sending economies and less outward migration. This study also analyzes the effect of remittances on labor market participation of left behind household heads, using a propensity score matching method. The results show that remittances have supported greater consumption of productive goods (such as durable goods, education and health), without discouraging labor supply of remittance-receiving family members.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet